GLANDULAR TRICHOME‐SPECIFIC WRKY 1 promotes artemisinin biosynthesis in Artemisia annua. Issue 1 (21st December 2016) - Chen, Minghui; Yan, Tingxiang; Shen, Qian; Lu, Xu; Pan, Qifang; Huang, Youran; Tang, Yueli; Fu, Xueqing; Liu, Meng; Jiang, Weimin; Lv, Zongyou; Shi, Pu; et al.
Summary: Artemisinin is a type of sesquiterpene lactone well known as an antimalarial drug, and is specifically produced in glandular trichomes of Artemisia annua . However, the regulatory network for the artemisinin biosynthetic pathway remains poorly understood. Exploration of trichome‐specific transcription factors would facilitate the elucidation of regulatory mechanism of artemisinin biosynthesis. The WRKY transcription factor GLANDULAR TRICHOME‐SPECIFIC WRKY 1 ( AaGSW1 ) was cloned and analysed in A. annua . AaGSW1 exhibited similar expression patterns to the trichome‐specific genes of the artemisinin biosynthetic pathway and AP2/ERF transcription factor AaORA . A β‐glucuronidase (GUS) staining assay further demonstrated that AaGSW1 is a glandular trichome‐specific transcription factor. AaGSW1 positively regulates CYP71AV1 and AaORA expression by directly binding to the W‐box motifs in their promoters. Overexpression of AaGSW1 in A. annua significantly improves artemisinin and dihydroartemisinic acid contents; moreover, AaGSW1 can be directly regulated by AaMYC2 and AabZIP1, which are positive regulators of jasmonate (JA)‐ and abscisic acid (ABA)‐mediated artemisinin biosynthetic pathways, respectively. These results demonstrate that AaGSW1 is a glandular trichome‐specific WRKY transcription factor and a positive regulator in the artemisinin biosynthetic pathway. Moreover, we propose that two trifurcate feed‐forward pathways involving AaGSW1, CYP71AV1 and AaMYC2 / AabZIP1 function in the JA/ABA response in A. annua .